Critical Process Relocation in Fragmented Multi-Building Food Production: Integrating Layout Redesign, Material Flow, and Economic Feasibility - Cholilie, Irvan Adhin; Mardhiyyah, Yunita Siti; Rakhmawati, Ainun (Department of Agro-industrial Technology, University of Brawijaya, 2025)
AbstractFacility layouts in small-scale food industries often develop incrementally without comprehensive flow planning, resulting in lengthy, discontinuous, and costly material movements. This gap arises because many studies still focus on single-building relayouts and fail to incorporate cross-building flow, critical process separation, and implementation feasibility into a single evaluation. This study aims to evaluate the fragmented layout of a krecek rambak (traditional Indonesian beef skin crackers) processing business in Mojokerto Regency, East Java Province, Indonesia, and to design a proposed layout that better aligns with the actual production flow. The study was conducted at a facility occupying three separate buildings with a manual handling system. The analysis included field observations, process mapping, a From-To Chart, rectilinear distance measurements, proximity analysis, layout alternative generation, material handling cost evaluation, and feasibility analysis. The results show a decrease in total movement distance from 5,837 m to 2,504 m, a decrease in movement frequency from 15 to 12, a decrease in daily material handling costs from IDR 403,294 to IDR 111,949, and a reduction in the critical path from 134.5 m to 12 m. These findings indicate that relocating critical processes is more effective than expanding general facilities in reducing costs and improving flow continuity. The practical implication lies in the availability of a more scalable, efficient, and feasible relayout decision-making basis for small-scale, incrementally expanding multi-building production systems.Keywords: facility layout, material flow, operational efficiency, relocation of critical processes, small food industry AbstrakTata letak fasilitas pada industri pangan skala kecil sering berkembang secara bertahap tanpa perencanaan aliran yang utuh sehingga perpindahan material menjadi panjang, terputus, dan mahal. Kesenjangan kajian muncul karena banyak penelitian masih berfokus pada relayout satu bangunan dan belum menggabungkan aliran lintas bangunan, pemisahan proses kritis, dan kelayakan implementasi dalam satu evaluasi. Penelitian ini bertujuan mengevaluasi tata letak terfragmentasi pada usaha pengolah krecek rambak di Kabupaten Mojokerto, Provinsi Jawa Timur, Indonesia dan merancang usulan tata letak yang lebih selaras dengan aliran produksi aktual. Studi dilakukan pada fasilitas yang menempati 3 bangunan terpisah dengan sistem penanganan manual. Analisis mencakup observasi lapangan, pemetaan proses, From-To Chart, pengukuran jarak rectilinear, analisis kedekatan, pembangkitan alternatif tata letak, evaluasi ongkos penanganan material, dan analisis kelayakan. Hasil menunjukkan total jarak perpindahan turun dari 5.837 m menjadi 2.504 m, frekuensi perpindahan berkurang dari 15 menjadi 12, ongkos penanganan material harian turun dari Rp403.294 menjadi Rp111.949, dan jalur kritis menyusut dari 134,5 m menjadi 12 m. Temuan ini menunjukkan bahwa relokasi proses kritis lebih efektif dibanding ekspansi fasilitas umum dalam menekan biaya dan memperbaiki kontinuitas aliran. Implikasi praktisnya terletak pada ketersediaan dasar keputusan relayout yang lebih terukur, efisien, dan layak diterapkan pada sistem produksi multi-bangunan skala kecil yang berkembang bertahap.Keywords: aliran material, efisiensi operasional, industri pangan kecil, relokasi proses kritis, tata letak fasilitas